Empowering Arts and Culture Teachers in Banjarnegara: Local Song Writing and Digital Innovation for Cultural Identity and Edu-Tourism - Sinaga, Syahrul Syah; Mumpuni, Restu Ayu; Mulianingsih, Ferani; Edi Nugroho, Antonius (Universitas Negeri Semarang, 2025)
This community service program aimed to empower Arts and Culture teachers in Banjarnegara through training on local song writing and the integration of digital platforms in music education. The initiative was motivated by the need to enhance teachers’ competence, strengthen local cultural identity, and promote creative learning innovations aligned with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 11 (Sustainable Cities and Communities). The program involved members of the MGMP Seni Budaya Banjarnegara and was implemented through a workshop model combining lectures, discussions, and practical sessions. Teachers were guided to compose children’s songs based on Banjarnegara’s local wisdom, such as traditional cuisine, natural attractions, and cultural values, which were later digitized and uploaded to the E-LokalTunes platform as digital learning materials. The outputs included at least one song per group, copyright registration (HKI), and a demonstration video to promote the works. The results showed that the program successfully improved teachers’ creativity, digital literacy, and confidence in integrating technology with cultural content. Overall, this initiative demonstrates how digital innovation can support cultural preservation, strengthen local identity, and serve as a sustainable and replicable model for arts-based education in other regions.